Lateral Cerebellar Nucleus Stimulation has Selective Effects on Glutamatergic and GABAergic Perilesional Neurogenesis After Cortical Ischemia in the Rodent Model. Issue 5 (27th September 2017) - Chan, Hugh H; Cooperrider, Jessica; Chen, Zhihong; Gale, John T; Baker, Kenneth B; Wathen, Connor A; Modic, Claire R; Park, Hyun-Joo; Machado, Andre G
Abstract: BACKGROUND: Chronic deep brain stimulation of the rodent lateral cerebellar nucleus (LCN) has been demonstrated to enhance motor recovery following cortical ischemia. This effect is concurrent with synaptogenesis and expression of long-term potentiation markers in the perilesional cerebral cortex. OBJECTIVE: To further investigate the cellular changes associated with chronic LCN stimulation in the ischemic rodent by examining neurogenesis along the cerebellothalamocortical pathway. METHODS: Rats were trained on the pasta matrix task, followed by induction of cortical ischemia and electrode implantation in the contralesional LCN. Electrical stimulation was initiated 6 wk after stroke induction and continued for 4 wk prior to sacrifice. Neurogenesis was examined using immunohistochemistry. RESULTS: Treated animals showed enhanced performance on the pasta matrix task relative to sham controls. Increased cell proliferation colabeled with 5'-Bromo-2'-deoxyuridine and neurogenic markers (doublecortin) was observed in the perilesional cortex as well as bilateral mediodorsal and ventrolateral thalamic subnuclei in treated vs untreated animals. The neurogenic effect at the level of motor cortex was selective, with stimulation-treated animals showing greater glutamatergic neurogenesis but significantly less GABAergic neurogenesis. CONCLUSION: These findings suggest that LCN deep brain stimulation modulates postinjury neurogenesis, providing a possible mechanistic foundation for the associated enhancement in poststroke motor recovery.